A Barbeque-Analog Route to Carbonize Moldy Bread for Efficient Steam Generation - Zhang, Yaoxin; Ravi, Sai Kishore; Vaghasiya, Jayraj Vinubhai; Tan, Swee Ching (iScience, 2018)
Sustainable reconversion of the large quantities of food waste generated every day is pivotal for a green urban development in future. Herein, we put forth a sustainable and cost-effective way to repurpose a commonly used food waste for solar steam generation, an important part of water desalination. Making use of moldy bread, a new route for steam generation is demonstrated. The moldy bread was converted into a solar absorber by a simple and cost-effective carbonization process mimicking outdoor barbeque cooking. Carbonizing food waste to facilitate better absorption of sunlight for effective evaporation of water is an unprecedented concept in this field. Interestingly, the carbonized bread repurposed from the food waste served as an effective solar steam generator with an efficiency as high as 71.4% under 1 sun illumination. The structural and thermal absorption properties of the carbonized bread facilitated efficient solar energy absorption, heat management, and water transpiration in the system. [Display omitted] •Barbeque-analog route provides feasibility of carbonization of natural materials•Carbonized moldy bread enables sustainable reconversion of food wastes•The evaporation efficiency stays high even at high relative humidity Energy Resources; Food Waste; Energy Materials